High-field electrodynamics - Hartemann, Frederic V (CRC, 2015)
Presents an introduction to high-field electrodynamics, from its fundamentals to some of its important modern applications. This discusses some of the ramifications of electrodynamics in areas ranging from quantum optics and the Einstein-Podolsky-Rosen paradox to rotating black holes, and the Bohm-Aharanov effect.